2010
DOI: 10.1158/1078-0432.ccr-10-0376
|View full text |Cite
|
Sign up to set email alerts
|

Foxo3a Suppression of Urothelial Cancer Invasiveness through Twist1, Y-Box–Binding Protein 1, and E-Cadherin Regulation

Abstract: Purpose: Invasion and metastasis are key steps in the progression of urothelial cancer (UC) into a critical disease. Foxo3a is a member of the Foxo transcription factor family that modulates the expression of various genes. We aimed to elucidate the role of Foxo3a in UC invasion.Experimental Design: Foxo3a mRNA and protein expressions in UC samples were investigated by gene expression assays and immunohistochemistry, respectively. Foxo3a expression was compared with clinicopathologic characteristics and patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 40 publications
3
68
0
Order By: Relevance
“…In fact, FOXO3a has been implicated in metastasis inhibition. For example, it has been shown that silencing FOXO3a in urothelial cells leads to increased cell motility, and that decreased FOXO3a expression is indicative of poor prognosis in patients with urothelial carcinomas (53). Similarly, ΔNp63α ablation in urothelial carcinoma cells results in increased cell motility (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, FOXO3a has been implicated in metastasis inhibition. For example, it has been shown that silencing FOXO3a in urothelial cells leads to increased cell motility, and that decreased FOXO3a expression is indicative of poor prognosis in patients with urothelial carcinomas (53). Similarly, ΔNp63α ablation in urothelial carcinoma cells results in increased cell motility (62).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Akt directly phosphorylates and inhibits nuclear translocation as well as transactivation activity of the FOXO family of proteins, including FOXO3a (also known as FKHRL1) and FOXO1 (also known as FKHR), which have been shown to play a role in regulating cell migration and invasion (53,54). We investigated whether FOXO transcription factors are involved in regulation of ΔNp63α expression.…”
mentioning
confidence: 99%
“…The repression of p300 was associated with Twist1 up-regulation and E-cadherin reduction by Foxo3a-knockdown in KK47 cell line. These results suggest a putative correlation between p300 and Twist1 in the modulation of urothelial cancer invasiveness [11]. Epigenetic activation of Twist1 was confirmed by histone acetyltransferase CBP, which cooperated with metadherin to increase Twist1 expression in breast cancer [12].…”
Section: Acetylation Of Twistmentioning
confidence: 71%
“…FOXO3a negatively regulates Twist1 and Y-box-binding protein 1 (YB-1), and positively regulated E-cadherin in With FOXO3a PAX3 acts as a prognostic factor [94].…”
Section: Urothelial Cancermentioning
confidence: 99%
“…Similarly, PAX3 can modulate the expression of FOXO3, another type of transcription factor that belongs to the FOXO family that are involved in multiple signaling pathways and plays critical roles in a number of physiologic and pathologic processes [97]. Cancer patients with low FOXO3a expression had poor disease-free survival, cancer-specific survival, and overall survival [94].…”
Section: Foxo-pax3 Association In Tumor Suppressionmentioning
confidence: 99%